Alkaloid Profiling, Anti-Enzymatic and Antiproliferative Activity of the Endemic Chilean Amaryllidaceae Phycella cyrtanthoides - Carlos Fernández-Galleguillos; Javier Romero-Parra; Adrián Puerta; José M. Padrón; Mario J. Simirgiotis (Metabolites, 2022)
This research aims to identify the alkaloid profile and to evaluate the enzyme inhibitory potential and antiproliferative effects of the Amaryllidaceae plant Phycella cyrtanthoides. The alkaloid extracts from bulbs and leaves were analyzed using ultrahigh performance liquid chromatography orbitrap mass spectrometry (UHPLC-Orbitrap-MS) analysis. A total of 70 alkaloids were detected in the P. cyrtanthoides’ extracts. The enzyme inhibition potential against cholinesterases (AChE: acetylcholinesterase, and BChE butyrylcholinesterase) and tyrosinase were studied. Bulbs displayed the best IC50 values against AChE (4.29 ± 0.03 µg/mL) and BChE (18.32 ± 0.03 µg/mL). These results were consistent with docking experiments with selected major compounds in the active sites of enzymes, while no activity was observed against tyrosinase enzyme. Antiproliferative effects were investigated against human cervical (HeLa), lung (A549, SW1573), colon (WiDr), and breast (HBL-100, T-47D) tumor cell lines. Bulbs and leaves were active in all cell lines (GI50 < 2.5 µg/mL). These findings suggest that the endemic Chilean plant P. cyrtanthoides contains diverse types of bioactive alkaloids with antiproliferative activities and inhibitory effects with potential therapeutic applications for neurodegenerative diseases